Implementasi Supervisi Pendidikan dalam Meningkatkan Mutu Pembelajaran di MAN 3 Kediri - Miftahul Ngulya; Asep Kurniawan (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
Educational supervision is all assistance from the headmaster of madrasa aimed at the development of teachers and other school personnel in achieving educational goals, it is in the form of encouragement, guidance, and opportunities for the growth of the skills and abilities of teachers. Based on this, this study aims to determine the implementation of educational supervision in improving the quality of learning in MAN 3 Kediri. The method used in data collection is observation, interview and documentation, while the data analysis technique uses a descriptive qualitative research approach, which is interpreted through descriptive explanations as a conclusion about supervision in improving the quality of learning. From the results of the study, it can be concluded that: (1) Implementation of educational supervision is carried out by compiling a program involving all citizens and overall, conducting upgrading through class visits, class observations, MGMP with mutual visits, training/workshops, evaluation and follow-up; (2). Improving the quality of learning through collaboration with teachers in strengthening the curriculum and developing learning tools, providing learning resources, tools and various teaching and learning facilities; (3) Implementation of educational supervision in improving the quality of learning through guidance and curriculum development, improving teaching and learning processes, and efforts to enhance the quality of teachers through coaching and up grading; (4) Obstacles to the Implementation of educational supervision in improving the quality of learning, namely: some teachers have not been able to deliver the material well, impromptu activities, facilities and infrastructure are damaged, coaching is often done on holidays. While the supporting factors are as follows: guidance on the content and concepts of curriculum thinking, internet facilities, madrasa books, socialization, certified teachers, adequate facilities and infrastructure in carrying out the teaching and learning process